Characterizations of the Secondary Metabolites of the Sea Squirt Diplosoma listerianum Milne-Edwards, 1841) (Ascidiacea, Enterogona) and its Associated Micro-organisms - Qurashi, Naif Al (Indian Journal of Pharmaceutical Education and Research, 2024)
Background The biochemistry of secondary metabolites of marine origin has been identified as a promising area for obtaining new and potent pharmaceutical agents. These secondary metabolism molecules may have important functions such as anti-biotic and anti-parasitic activity, mediate symbiotic relationships between organisms and even have reproductive functions, representing a great ecological advantage for the survival of marine organisms. Aim This study aimed to characterize the secondary metabolites of the sea squirt Diplosoma listerianum and its associated micro-organisms. Materials and Methods The squirts were frozen, dried, weighed, roughly crushed and extracted using methanol and dichloromethane (1:1). The crude extract was dissolved in methanol and fractionated in four solvents of increasing polarity: saturated hexane, acetic ester, butyl alcohol and water. The active substances were isolated by liquid chromatography, purified and their structures determined. Bacteriostatic action against the crude extract was assessed using longitudinal in vitro growth in Müller-Hinton broth. Results D. listerianum’s crude extract showed antibiotic activity against various pathogenic microorganisms. Analysis of variance and Tukey’s multiple comparison tests indicated significant differences among exposure times. Mouse fibroblasts exposed to the crude extract showed fragmented and sickle-shaped nuclei, visible centrosomes, abnormal multipolar mitotic spindles and endoplasmic reticulum vacuolization. The phytagel assay showed a correlation between the gel’s algal density and associated organism numbers. The protein tyrosine kinase assay showed that the crude extract had enzyme-inhibiting properties. Preparative high-performance liquid chromatography, Sephadex column chromatography, high-resolution electrospray ionization mass spectrometry and electron impact mass spectra identified zeaxanthin, tubastrine (an epidermal growth factor receptor inhibitor), inosine, guanosine, oxazolidin-2-one, LL-PAA216 and 2-aminododecan-3-ol. Conclusion Marine biotechnology generates technological products from the diversity of marine organisms and their strategic adaptations to the extreme conditions of the seas and, in turn, presents itself as a promising source of bioproducts and processes, being able to solve issues in areas such as health, food safety, cosmetics, agriculture, pollution control, climate and industry, among others.
Keywords: Diplosoma listerianum; Bacteriostatic action; Mouse fibroblasts; Field study; Aromatic compounds